2017 National Quality and Safety Education for Nurses Faculty Survey Results. (September 2017) - Altmiller, Gerry; Armstrong, Gail
Abstract : The Quality and Safety Education for Nurses (QSEN) national initiative, started in 2005, has supported the adoption and integration of updated quality and safety competencies in nursing education. However, faculty needs regarding QSEN competency integration, and the degree to which QSEN competencies are reflected in current nursing curricula, have not been assessed nationally. This study (N = 2037) reports the findings of the 2017 National QSEN Faculty Survey and discusses implications for nurse educators and programs of nursing education. Abstract : Supplemental digital content is available in the text.